Evaluation of knowledge, awareness, treatment and prevention towards pregnancy induced hypertension among the pregnant women in Bangladesh: a hospital based cross-sectional study - Zohora, Fatama Tous; Aktar, Salma; Hossain, M. Imam (International Journal Of Community Medicine And Public Health, 2022)
Background: Pregnancy induced hypertension (PIH) is one of the major causes of maternal and neonatal morbidity, mortality and premature birth. 99% of the maternal deaths is occurring in developing countries like Bangladesh. Almost 12% of the maternal deaths is associated with hypertensive disorders such as PIH in pregnancy. It can be prevented by proper knowledge, awareness of the disease and its complications. We investigated the knowledge, awareness of PIH and its related factors during pregnancy among the pregnant women in Tangail, Bangladesh. Methods: A descriptive cross-sectional study among 200 pregnant women in between March 2021 to June 2021 was conducted by using a questionnaire at Sheikh Hasina Medical College Hospital (SHMC) of Tangail district, Bangladesh. Factors associated with the knowledge and awareness of PIH were investigated separately using Chi square test. Results: In this study, 92.5% of the pregnant women had heard about PIH and 10.5% pregnant women had PIH. Age group 30-35, >35 and post graduate respondents were more knowledgeable and aware than others about PIH and urban respondents were highly knowledgeable and aware to PIH compare to rural respondents. The age of the respondents, area of residence, educations, occupations, socioeconomic status were found to be significantly associated with PIH knowledge and awareness. Conclusions: The study result showed that there is need to increase public knowledge and awareness about PIH. Health educational programs throughout the rural and urban areas need to be intensified to reduce PIH-related deaths among the pregnant women in Bangladesh.